“Coopetition” in the presence of team and individual incentives: Evidence from the advice network of a sales organization - Christian Homburg; Theresa R. Schyma (née Morguet); Sebastian Hohenberg; Yashar Atefi; Robin-Christopher M. Ruhnau (Journal of the Academy of Marketing Science, 2023)
Team and individual incentives are ubiquitous in sales, but little is known about their impact on collaboration when they are applied simultaneously. The presence of both types of incentives creates a "coopetitive" environment, where forces of collaboration and competition coexist. We examine how such environments impact the likelihood (Study 1) and the effectiveness (Study 2) of collaboration in the form of advice exchange. Exponential random graph modeling (ERGM) of network data of 540 salespeople reveals that individual incentives promote advice seeking but discourage advice giving, and team incentives stimulate advice giving but reduce advice seeking (Study 1). We also find that the effectiveness of advice depends on advice givers (Study 2). In particular, when advice givers have diverse team incentives, the advice is more effective and the need for additional advice is reduced, but when advice givers have diverse individual incentives, the advice is less effective and additional advice helps.
Keywords: 330; Advice seeking; Advice giving; Sales; Social network analysis; Exponential random graph models; Team incentives; Individual incentives